Isoespintanol, a monoterpene isolated from oxandra cf xylopioides, ameliorates the myocardial ischemia-reperfusion injury by AKT/PKCε/eNOS-dependent pathways - González Arbeláez, Luisa Fernanda (2019)
To determine the actions of isoespintanol (Isoesp) on post-ischemic myocardial and mitochondrial alterations. Hearts removed from Wistar rats were perfused by 20 min. After this period, the coronary flow was interrupted by half an hour and re-established during 1 h. In the treated group, Isoesp was administered at the beginning of reperfusion. To assess the participation of e isoform of protein kinase C (PKCe), protein kinase B (PKB/Akt), and nitric oxide synthase (NOS), hearts were treated with Isoesp plus the respective inhibitors (chelerythrine, wortmannin, and N-nitro-l-arginine methyl ester). Cell death was determined by triphenyl tetrazolium chloride staining technique. Post-ischemic recovery of contractility, oxidative stress, and content of phosphorylated forms of PKCe, Akt, and eNOS were also examined. Mitochondrial state was assessed through the measurement of calcium-mediated response, calcium retention capacity, and mitochondrial potential. Isoesp limited cell death, decreased post-ischemic dysfunction and oxidative stress, improved mitochondrial state, and increased the expression of PKCe, Akt, and eNOS phosphorylated. All these beneficial effects achieved by Isoesp were annulled by the inhibitors. These findings suggest that activation of Akt/eNOS and PKCe signaling pathways are involved in the development of Isoesp-induced cardiac and mitochondria tolerance to ischemia-reperfusion.